El terremoto como noticia: relaciones de sucesos y otros textos del temblor de 16801 - Rueda Ramírez, Pedro; Fernández Chaves, Manuel (Estudios sobre el Mensaje Periodístico, 2008)
A particular event as the earthquake of 1680 caused widely news spreading in a way extraordinary and in cities like Malaga, Granada and Seville were published some news-pamphlets with stories about what had happened. The growing interest in these forms, from different approaches, focusing on our case in the history of cultural and the press communication, will lead to a reconstruction (preparing a catalogue of texts related to the earthquake) and an attempt to order the series with the aim of detecting the movement of news and its possible impact on readers of different cities.